Dissecting thermotolerance traits of tomato (Solanum lycopersicum L.) genotypes for crop improvement - Anjali Joy S. L.; Deepthy Antony P.; Joseph, Jiji; Parvathi M. S.; Augustine, Rehna (Journal of Tropical Agriculture, 2025)
High temperature being a major abiotic stress affecting crop production, incorporating thermotolerance is a priority in crop improvement. Screening of 30 tomato genotypes for thermotolerance traits and yield was done under laboratory and field conditions in favourable and summer seasons. Thermotolerance traits namely, pollen and style characters and membrane stability, along with major yield characters were evaluated. Individual traits, combination of traits, and per cent change with season, were considered to identify superior genotypes. AVTO 0922, AVTO 1725, EC 523851, EC 528368, EC 620486, EC 620488, and Vellayani Vijay displayed superior membrane stability coupled with above average pollen viability and germination in laboratory screening. Per cent change in tolerance traits in summer compared to favourable season was lower in EC 528360, EC 528368, EC 523851, EC 636872, EC 620494, and EC 549819. Akshaya, Anagha, Arka Rakshak, AVTO 1707 and AVTO 1314 which had higher fruit set per cent, fruit yield per plant and average fruit weight can be utilised for yield improvement.